Safety and immunogenicity of an inactivated SARS-CoV-2 vaccine in healthy adults aged 18 years or older: A randomized, double-blind, placebo-controlled, phase 1/2 trial. (August 2021) - Guo, Wanshen; Duan, Kai; Zhang, Yuntao; Yuan, Zhiming; Zhang, Yan-Bo; Wang, Zejun; Zhao, Dongyang; Zhang, Huajun; Xie, Zhiqiang; Li, Xinguo; Peng, Cheng; Zhang, Wei; et al.
Abstract: Background: We aimed to assess the safety and immunogenicity of an inactivated vaccine against COVID-19 in Chinese adults aged ≥18 years. Methods: This is an ongoing randomized, double-blind, placebo-controlled, phase 1/2 clinical trial among healthy adults aged ≥18 years in Henan Province, China. Participants ( n  = 336 in 18–59 age group and n  = 336 in ≥60 age group) were enrolled between April 12 and May 17 2020, and were equally randomized to receive vaccine or placebo (aluminum hydroxide adjuvant) in a three-dose schedule of 2·5, 5, or 10 µg on days 0, 28, and 56. Another 448 adults aged 18–59 years were equally allocated to four groups (a one-dose schedule of 10 µg, and two-dose schedules of 5 µg on days 0 and 14/21/28) and received vaccine or placebo (ratio 3:1 within each group). The primary outcomes were 7-day post-injection adverse reactions and neutralizing antibody titres on days 28 and 90 after the whole-course vaccination. Trial registration: www.chictr.org.cn #ChiCTR2000031809. Findings: The 7-day adverse reactions occurred in 4·8% to 32·1% of the participants in various groups, and most adverse reactions were mild, transient, and self-limiting. Twenty participants reported 68 serious adverse events which were judged to be unrelated to the vaccine. The 90-day post-injection geometric mean titres of neutralizing antibody ranged between 87 (95% CI: 61–125) and 129 (99–169) for three-dose schedule among younger and older adults; 20 (14–27), 53 (38–75), and 44 (32–61) in 5 µg days 0 and 14/21/28 groups, respectively, and 7 (6–9) in one-dose 10 µg group. There were no detectable antibody responses in all placebo groups. Interpretation: The inactivated vaccine against COVID-19 was well tolerated and immunogenic in both younger and older adults. The two-dose schedule of 5 µg on days 0 and 21/28 and three-dose schedules on days 0, 28, and 56 could be further evaluated for long-term safety and efficacy in the phase 3 trials. Funding: The study was funded by the National Program on Key Research Project of China (2020YFC0842100) and Major Science and Technology Project of the National New Drug Development of China (2018ZX09734-004).